2021
DOI: 10.36490/agri.v4i2.154
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization the Omission One Test as Determination Limiting Factors for Maize Biomass (Zea mays L.)

Abstract: Introduction: The research was aimed to obtain information on the impact of omission one test fertilization as a determination limiting factors for the growth and biomass of maize in variety Bonanza F1. Materials and Methods: The research was located in the experimental field, Faculty of Agriculture and Animal Husbandry, Universitas Tjut Nyak Dhien, Medan from December 2020 until February 2021. The research was applied by Randomized Block Design in non-factorial through fertilization of omission o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Studies on nutrient-limiting factors in maize plants are limited in scientific reports. [11] found that the limiting factor for the vegetative growth of maize plants was the absence of nitrogen fertilization. [12] added that the highest percentage of limiting factors for maize plants sequentially found without fertilization, P+K; N+K; and N+P were 6.31-105.89; 7.73-87.01; 38.03-99.70; and 73.78-113.22% respectively, compared to N+P+K.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on nutrient-limiting factors in maize plants are limited in scientific reports. [11] found that the limiting factor for the vegetative growth of maize plants was the absence of nitrogen fertilization. [12] added that the highest percentage of limiting factors for maize plants sequentially found without fertilization, P+K; N+K; and N+P were 6.31-105.89; 7.73-87.01; 38.03-99.70; and 73.78-113.22% respectively, compared to N+P+K.…”
Section: Introductionmentioning
confidence: 99%